Survey of Alimentary Radiology Findings in the North-east of Scotland Region (1967-70). Issue 5805 (8th April 1972) - Petrie, J. C.; Needham, C. D.; Gillanders, L. A.
Abstract : This report describes a survey of all barium contrast radiological examinations carried out in the years 1967-70 by the unit that serves 99% of the adult population of North-east Scotland. The survey method used yields useful estimates, not otherwise available, of the occurrence of some forms of alimentary lesions within a whole community. Rates of occurrence by age and sex were recorded for all lesions. The data on peptic ulceration, were compared with those from South-east and from North England, and this showed that duodenal, but not gastric, ulceration is much commoner in North-east Scotland. Occurrence rates for most lesions have been nearly unchanged throughout the four years of survey. The data provide a measure of the work load for these radiological examinations for a given population.